Zum Bestand und Struktur der exozentrischen Konstruktionen im Norwegischen (bokmål) - Awedykowa, Sława (Studia Germanica Posnaniensia, 2018)
The article is an attempt at component analysis of compound words in Norwegian. The author restricted her material to exocentric compounds.